1990
DOI: 10.1095/biolreprod43.6.1079
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic Ductal System in Rats: Regional Variation in Morphological and Functional Activities1

Abstract: The rat prostate is a complex ductal system with branches and subbranches extending from one end to another. Owing to the relative distance of various regions of the duct from the urethra, the entire length of the ductal system can be arbitrarily divided into three segments, i.e., the proximal, intermediate, and distal segments. The present study was carried out to assess the regional variation in cellular activities in this ductal system. Ventral prostates from adult Sprague-Dawley rats were dissected so that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
95
0
28

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(139 citation statements)
references
References 13 publications
16
95
0
28
Order By: Relevance
“…DeKlerk and Coffey (1978) and Sugimura et al, (1986a,b) reported that the epithelial and stromal cells of different regions of the prostatic lobes respond differently to androgenic privation and stimulation, suggesting a functional heterogeneity inside the lobe. Therefore, in addition to the main ducts in prostate lobes of some rodents already studied, three morphologically and functionally distinct regions called distal, intermediate, and proximal, according to the position occupied in relation to the urethra, have been recognized (Lee et al, 1990;Banerjee et al, 1994;Nemeth and Lee, 1996). Nemeth and Lee (1996) have described how the regional differences along the duct system of the VL in rats, even in the acinar epithelium as in the stromal compartment, reflect differences in secretion levels, proliferation, and cellular death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DeKlerk and Coffey (1978) and Sugimura et al, (1986a,b) reported that the epithelial and stromal cells of different regions of the prostatic lobes respond differently to androgenic privation and stimulation, suggesting a functional heterogeneity inside the lobe. Therefore, in addition to the main ducts in prostate lobes of some rodents already studied, three morphologically and functionally distinct regions called distal, intermediate, and proximal, according to the position occupied in relation to the urethra, have been recognized (Lee et al, 1990;Banerjee et al, 1994;Nemeth and Lee, 1996). Nemeth and Lee (1996) have described how the regional differences along the duct system of the VL in rats, even in the acinar epithelium as in the stromal compartment, reflect differences in secretion levels, proliferation, and cellular death.…”
Section: Discussionmentioning
confidence: 99%
“…In the hopping mouse, the VL is the only component of the prostatic complex (Tsonis et al, 1981). Thus several studies have reported that there are considerable differences in the ductal array, histology, and hormonal sensitivity among the prostatic complex lobes in laboratory rodents (Jesik et al, 1982;Sugimura et al, 1986a;Lee et al, 1990;Hayashi et al, 1991;Banerjee et al, 1994;Kinbara and Cunha, 1996). It is known that these differences are, at least in part, a consequence of morphogenesis (Sugimura et al, 1986a), and recently the Hox genes have been indicated as distinct expression of genetic patterns involved in lobe identity (Huang et al, 2004).…”
mentioning
confidence: 99%
“…Finally, the proximal ducts of the mouse prostate express Cathepsin D, a marker of apoptosis (Lee et al 1990). No equivalent zone has been demonstrated in the human prostate.…”
Section: Gfp Expression Is Restricted To the Ductal Tips Of Adult Moumentioning
confidence: 99%
“…Second, while basal cells comprise the majority of proliferating cells in the human prostate, most proliferative activity in the mouse prostate is localized to columnar cells lining the distal regions of the prostatic ducts (Lee et al 1990;Sugimura et al 1996). Third, secretory activity in the murine prostate is maximum in intermediate regions of the duct, compared to humans in which no such regional heterogeneity has been reported (Lee et al 1990). …”
Section: Gfp Expression Is Restricted To the Ductal Tips Of Adult Moumentioning
confidence: 99%
“…A majority of proliferating cells are located at the tips of the ducts, whereas the proximal ducts attached to the urethra contain a high percentage of apoptotic cells (11,12). Secretory activity has been proposed to be concentrated in the intermediate regions of the duct.…”
mentioning
confidence: 99%